Beware of vested interests: Epistemic vigilance improves reasoning about scientific evidence (for some people). - Lukas Gierth; Rainer Bromme (PLoS ONE, 2020)
In public disputes, stakeholders sometimes misrepresent statistics or other types of scientific evidence to support their claims. One of the reasons this is problematic is that citizens often do not have the motivation nor the cognitive skills to accurately judge the meaning of statistics and thus run the risk of being misinformed. This study reports an experiment investigating the conditions under which people become vigilant towards a source's claim and thus reason more carefully about the supporting evidence. For this, participants were presented with a claim by a vested-interest or a neutral source and with statistical evidence which was cited by the source as being in support of the claim. However, this statistical evidence actually contradicted the source's claim but was presented as a contingency table, which are typically difficult for people to interpret correctly. When the source was a lobbyist arguing for his company's product people were better at interpreting the evidence compared to when the same source argued against the product. This was not the case for a different vested-interests source nor for the neutral source. Further, while all sources were rated as less trustworthy when participants realized that the source had misrepresented the evidence, only for the lobbyist source was this seen as a deliberate attempt at deception. Implications for research on epistemic trust, source credibility effects and science communication are discussed.